The Influence of Organizational Culture and Work Motivation on the Work Productivity of Lecturers at Private Universities in Central Kalimantan - Vivi Pancasari Kusumawardani; Ani Purwaningsih; Rini Rahmawati; Fanlia Prima Jaya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Aim: This study aims to determine the influence of Organizational Culture and Work Motivation on the Work Productivity of Lecturers at Universities in Central Kalimantan. Method: This research employs a quantitative method by processing information obtained from questionnaires requiring measurement. The population in this study consists of 23 Private Universities in Central Kalimantan, with a total of 809 lecturers. Using the Slovin formula, a sample of 89 respondents was obtained. The study utilizes multiple linear regression analysis techniques using SMART PLS 4.0.9.2 software. Result and discussions: The results of this study found that Organizational Culture has a significant partial effect on Work Productivity, Work Motivation also has a significant partial effect on Work Productivity, and Organizational Culture and Work Motivation simultaneously have a significant effect on the Work Productivity of Lecturers at Private Universities in Central Kalimantan. Conclusion: Based on the analysis of the results and discussions, it can be concluded that Organizational Culture partially has a significant effect on the Work Productivity of lecturers at Private Higher Education Institutions in Central Kalimantan. Work Motivation partially has a significant effect on the Work Productivity of lecturers at Private Higher Education Institutions in Central Kalimantan. Organizational Culture and Work Motivation simultaneously have a significant effect on the Work Productivity of lecturers at Private Higher Education Institutions in Central Kalimantan.